1990
DOI: 10.1093/nar/18.5.1249
|View full text |Cite
|
Sign up to set email alerts
|

The lack of protamine 2 (P2) in boar and bull spermatozoa is due to mutations within the P2 gene

Abstract: The nuclei of spermatozoa in all mammals examined so far contain P1 protamine. A second protamine variant, protamine P2, has to date been isolated only from human and murine spermatozoa where it represents the major fraction of basic nuclear protein. In order to elucidate the reason for this unusual distribution of the protamine variants among mammals we have investigated the expression of protamine P2 in boar and bull. It can be shown that also in these species protamine 2 is transcribed and translated on low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
7

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 36 publications
1
45
0
7
Order By: Relevance
“…2, amino acid sequences for the nine primate P2 pro-protamines predicted from the coding sequences of their cognate genes are compared. In view of the highly variable expression of the pro-P2 gene in mammals [8,251, the presence of a pro-P2 gene sequence in the non-human genomes does not imply that the genes are expressed. The mean length of pro-P2 is 101 residues with an increase of one residue to 102 in M-nemistrina and a decrease to 99 residues in red howler (A. seniculus).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, amino acid sequences for the nine primate P2 pro-protamines predicted from the coding sequences of their cognate genes are compared. In view of the highly variable expression of the pro-P2 gene in mammals [8,251, the presence of a pro-P2 gene sequence in the non-human genomes does not imply that the genes are expressed. The mean length of pro-P2 is 101 residues with an increase of one residue to 102 in M-nemistrina and a decrease to 99 residues in red howler (A. seniculus).…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal coding sequence of bull P2 also contains several mutations that lead to a reduction of the number of basic residues through their replacement by neutral and hydrophobic residues that may decrease the binding of bull P2 to DNA [8].…”
Section: N I ___)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients possessing a high percentage of mature sperm with single-stranded DNA are still capable of fertilization, as Ab patients had a median fertilization rate of 25.0%. Previous studies have supported this finding (23,36)° Studies carried out on animals which possess the P2 gene but produce no or low levels of protamine 2 (12,13,38,39) have suggested that reduction in either P 1 or P2 may be explained by either reduced protamine transcription and translation or unstable products as a result of failed posttranscriptional modification. Lack of P2 in the boar has been shown to be due to mutations within the P2 gene (31).…”
Section: Discussionmentioning
confidence: 72%
“…PI is found throughout the animal kingdom, whereas P2 has been isolated only in humans and a few other mammals (mouse, hamster and stallion) studied to date (7)(8)(9)(10)(11)(12). The P2 gene has, however, been shown to exist in the genomes of bull and boar (13), despite their lacking the P2 protein. In human sperm of fertile men P1 and P2 are found at the ratio of approximately 1:1 (2).…”
Section: Introductionmentioning
confidence: 99%